Catalisadores de Ni/Al2O3 promovidos com Au e Ag aplicados à reforma a vapor do metano - Rocha, Kleper de Oliveira (Universidade Federal de São Carlos, 2005)
15%Ni/Al2O3 catalysts was obtained by impregnation with Ni(NO3)2 aqueous solution and promoted with Au and Ag. The Au was successively impregnated with aqueous solution of [Au(NH3)4](NO3)3. The Ag was coimpregnated with aqueous solution of AgNO3- Ni(NO3)2. The effect of Ag and Au on the catalytic behavior of Ni/Al2O3 catalysts in the reaction of steam reforming of CH4 was elucidate. The catalysts were characterized by temperatureprogrammed reduction (TPR), temperature-programmed dessorption of H2 (TPDH2) and Fourier transform infrared spectroscopy (FTIR) of CO adsorption. TPR results indicated that NiO is in weak interaction with support and the temperature reduction of NiO is independent of Ag and Au presence. FTIR data of CO adsorbed showed that Ag and Au suppress the CO adsorption in poli-coordination relative to the linear CO. Ag or Au on the Ni surface presents a determinant role in the block of graphitic carbon formation in the reaction of steam reforming of CH4. The fit of Arrhenius equation to rate of the total reaction showed a compensation effect between the apparent activation energy (Ea ap) and logarithmic of prefactor (k0). The linear increase of Ea ap with rise of lnk0 is observed increasing Ag and Au loading, which is followed by decreasing of the catalytic activity. Theses results suggest that the CHx intermediates, formed in the determinant stage of global velocity, show low interaction of with surface of Ni. The increase of the resistance for graphite formation by presence of Ag or Au is mainly attributed to the block of highly uncoordinated Ni atoms, which are higher activity to activation of CH4 and act as nucleation site for graphite formation.
Keywords: Catalisadores; Cinética; Preparação de amostra (química analítica); Energia de ativação; Efeito de compensação; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA